2005
DOI: 10.1128/aem.71.5.2705-2712.2005
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Quartz Crystal Microbalance To Investigate the Antiadhesive Potential of N -Acetyl- l -Cysteine

Abstract: The reduction of bacterial biofilm formation on stainless steel surfaces by N-acetyl-L-cysteine (NAC) is attributed to effects on bacterial growth and polysaccharide production, as well as an increase in the wettability of steel surfaces. In this report, we show that NAC-coated stainless steel and polystyrene surfaces affect both the initial adhesion of Bacillus cereus and Bacillus subtilis and the viscoelastic properties of the interaction between the adhered bacteria and the surface. A quartz crystal microba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 53 publications
4
51
1
4
Order By: Relevance
“…These findings agrees with that of Zheng et al [11] who observed by electron microscope a fine, granular, electrondense, ruthenium red-positive layer on the surface of pharyngeal epithelial cells; this layer was absent on cell surfaces treated with mucoregulating drugs; they owed the antiadherent effect of some mucolytics to the disappearance of such molecules. However, our findings are consistent with those of Olofsson et al [34] who attributed the antiadherent activity of the mucolytic agent N-acetyl cysteine to reduction of microbial exopolysaccharide production. Taken together, the findings of the present study open up a new possibility of interfering with bacterial adhesiveness and its resulting pathogenicity by agents devoid of antibacterial activity.…”
Section: Discussionsupporting
confidence: 94%
“…These findings agrees with that of Zheng et al [11] who observed by electron microscope a fine, granular, electrondense, ruthenium red-positive layer on the surface of pharyngeal epithelial cells; this layer was absent on cell surfaces treated with mucoregulating drugs; they owed the antiadherent effect of some mucolytics to the disappearance of such molecules. However, our findings are consistent with those of Olofsson et al [34] who attributed the antiadherent activity of the mucolytic agent N-acetyl cysteine to reduction of microbial exopolysaccharide production. Taken together, the findings of the present study open up a new possibility of interfering with bacterial adhesiveness and its resulting pathogenicity by agents devoid of antibacterial activity.…”
Section: Discussionsupporting
confidence: 94%
“…Non-rigid binding leads to energy dissipation, which can be recorded simultaneously by QCM with dissipation monitoring (QCM-D) (Rodahl et al, 1995). This technique has been used in a wide range of adhesion studies (Olofsson et al, 2005;Otto et al, 1999;Otto & Silhavy, 2002).…”
Section: Measuring Adhesion At a Molecular Levelmentioning
confidence: 99%
“…NAC also adversely affects bacterial growth and polysaccharide production and disrupts disulfide bonds in mucus, reducing the viscosity of secretions. These properties may contribute to the prevention and disruption of biofilm around different polymeric and metallic surfaces (9,(19)(20)(21). Not only does NAC diminish the formation of biofilm by common pathogens (19,22,23), it also possesses some in vitro intrinsic antimicrobial activity against both Gram-positive and Gram-negative bacteria (24).…”
mentioning
confidence: 99%
“…Cell surface proteins and polysaccharide production by bacterial cells reportedly contribute to the formation of biofilm that can then protect pathogens by impeding both the penetration of antibiotics and the function of phagocytic immune cells, thus hindering the ability to combat colonizing pathogens (7)(8)(9).…”
mentioning
confidence: 99%